(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
In this work, we discussed certain relationships between the idea of -lifting modules and many other related types of modules, explained these relationships and provided criteria that make these modules comparable to -lifting modules. CONCLUSION It has addressed to the concept of -lifting and other related types of modules and analyze the relations between these different kinds of modules like g-local, ⨁-g-supplemented, g-supplemented, sgrs-modules, -module, ()-modules etc. The necessary conditions have been set to achieve equivalence between them and thus obtained equivalent definitions to the -lifting definition within certain conditions.